ROS function as an inducer of autophagy to promote granulocyte proliferation in Pacific oyster Crassostrea gigas. (October 2022) - Zhang, Dan; Dong, Miren; Song, Xiaorui; Qiao, Xue; Yang, Ying; Yu, Simiao; Sun, Wending; Wang, Lingling; Song, Linsheng
Abstract: Hematopoiesis is the biological process to generate new blood cells in the living body and reactive oxygen species (ROS) contribute significantly to the regulation of haematopoietic cell homeostasis. In the present study, the involvement of ROS in the proliferation of haemocytes was examined in Pacific oyster Crassostrea gigas . The ROS content in haemocytes increased significantly after lipopolysaccharide (LPS) treatment, but decreased after the treatment with antioxidant N -Acetyl-L-cysteine (NAC, a scavenger of ROS). The percentage of 5-ethynyl-2′-deoxyuridine labeled (EdU + ) granulocytes in total haemocytes significantly increased at 12 h (4.12-fold, p < 0.001) and 24 h (2.36-fold, p < 0.001) after LPS treatment, while decreased at 12 h (0.26-fold, p < 0.001) and 24 h (0.61-fold, p < 0.05) after NAC treatment, respectively. Meanwhile, the percentage of haemocytes with autophagosome positive signals significantly increased at 12 h (1.17-fold, p < 0.01) and 24 h (1.19-fold, p < 0.05) after LPS treatment, but significantly reduced at 12 h (0.41-fold, p < 0.001) and 24 h (0.28-fold, p < 0.001) after the NAC treatment, respectively. After ammonium chloride (NH4 Cl) treatment, the percentage of haemocytes with autophagosome and EdU + granulocytes significantly increased at 12 h, which was 1.27-fold ( p < 0.01) and 1.70-fold ( p < 0.01) of control group, respectively. These results collectively suggested that ROS produced after LPS treatment could act as an inducer for autophagy and involved in regulating the proliferation of some granulocytes in C. gigas. Highlights: The ROS level in haemocytes were significantly increased after LPS treatment. The elevated ROS induced LC3 conversion and autophagosome production in haemocytes to trigger autophagy. The proliferation activity of granulocytes increased significantly after the degradation of autophagosome was inhibited. ROS level mediated the autophagy to regulate the proliferation of granulocytes in oyster.